SYNTHESIS AND SCREENING OF ANTIMICROBIAL ACTIVITY OF TWO BROMO-3′,4′-DIMETHOXYCHALCONE DERIVATIVES - Gocić, Valentina; Marković, Ana; Krstić, Nikola; Lazarevic, Jelena (Acta medicae Medianae, 2023)
Bromochalcone derivatives were synthesized, structurally characterized and screened for their in vitro antibacterial activity against a panel of two Gram-positive (Bacillus subtilis ATCC 6633 and Staphylococcus aureus ATCC 6538) and two Gram-negative (Escherichia coli ATCC 8739 and Salmonella typhimurium ATCC 14028) laboratory control strains in a disc diffusion assay. The antimicrobial test revealed that 4-bromo-3′,4′-dimethoxysubstituted chalcone was active against two involved Gram-negative strains, exhibiting stronger bactericidal effect on E. coli (11 ± 0.3 mm) than on S. typhimurium (15 ± 0.7 mm). Such observed difference in activity highlighted A-ring position 4- as potentially favourable for creating effective Gram-negative antibacterial agents.